The link between Access to Renewable Energy and Development in Gutu District. - Maganga, Tafadzwa (Midlands State University, 2017)
Ending poverty and underdevelopment in rural areas of Zimbabwe has been a challenge for quite a long time. Government and other development partners have come up with various policies, programmes and projects to address the various forms of poverty manifesting in rural areas. As the process of development is dynamic and ongoing, this research paper on the link between access to renewable energy and rural development seeks to examine the feasibility of harnessing renewable energy for rural development drawing its inspiration from the Rural Sustainable Energy Development programme in Gutu District. The paper seeks to promote the use of renewable energy as a solution to energy poverty and poverty in general by examining some of the benefits that access to renewable energy can offer towards the development of rural communities in Zimbabwe. This is a qualitative research providing a clear picture of the various economic, social and political development effects to society as well as environmental sustainability issues as well as Challenges faced by rural communities in Zimbabwe in adopting renewable energy technologies. Recommendations to these problems are also part of the research.